Ageing with Smartphones in Urban Italy Care and community in Milan and beyond - Walton, Shireen (Ageing with Smartphones, 2021)
'Who am I at this (st)age? Where am I and where should I be, and how and where should I live?' These questions, which individuals ask themselves throughout their lives, are among the central themes of this book, which presents an anthropological account of the everyday experiences of age and ageing in an inner-city neighbourhood in Milan, and in places and spaces beyond.Ageing with Smartphones in Urban Italy explores ageing and digital technologies amidst a backdrop of rapid global technological innovation, including mHealth (mobile health) and smart cities, and a number of wider socio-economic and technological transformations that have brought about significant changes in how people live, work and retire, and how they communicate and care for each other. Based on 16 months of urban digital ethnographic research in Milan, the smartphone is shown to be a 'constant companion' in, of and for contemporary life. It accompanies people throughout the day and night, and through individual and collective experiences of movement, change and rupture. Smartphone practices tap into and reflect the moral anxieties of the present moment, while posing questions related to life values and purpose, identities and belonging, privacy and sociability. Through her extensive investigation, Shireen Walton argues that ageing with smartphones in this contemporary urban Italian context is about living with ambiguity, change and contradiction, as well as developing curiosities about a changing world, our changing selves, and changing relationships with and to others. Ageing with smartphones is about figuring out how best to live together, differently.